Transversal crack and delamination of laminates using XFEM - Abdullah, Nur Azam; Curiel-Sosa, Jose Luis; Taylor, Zeike A.; Tafazzolimoghaddam, Behrooz; Martinez Vicente, J.L.; Zhang, Chao (Elsevier, 2017)
This paper offers a new insight into the computational modelling of crack and delamination of carbon fiber composite. Both transversal cracks (intralaminar) and delamination (interlaminar) are modelled with Extended Finite Element Method (XFEM). Constitutive and fracture laws are integrated to model the initiation of crack or delamination, and their subsequent evolution. The study includes the size effect assessment of composite due to the increment of composite thickness. The results are in close agreement between the experimental and analytical data of each specimen modelled based on the size of the carbon fiber composite volume.